A NOVEL SOLAR DRYER FOR DRYING OF MAIZE - SHARMA, KIRTIKA; kothari, Surendra; Panwar, Narayan lal (International Journal of Applied Power Engineering (IJAPE))
This research paper deals with the design and development of a cylindrical solar drying system feasible for drying of maize cobs. Drying is a highly energy intensive post-harvest process which consumes lots of electricity when conventional energy is used. Thus this research aims to substitute the energy required for drying by non-conventional means. Solar dryers are efficient and economic means of uniform drying agricultural food products which maintains the product quality along with decreasing drying and marketing time and also burden on farmer?s pocket for drying. Maize is considered for the research work here as it is a most important staple crop of India and has largest source of calorie among food grains. The demand for dried maize grains is increasing along with its nutritionally enriched value added products indicating the growth potential of maize industry in developing countries. An effect has been done to improve the dryer so that the drying process can be made more efficient and effective. The developed dryer proved to be technically and economically feasible with a high percentage of internal rate of return ie; 66 per cent. The results of solar assisted dryer when compared with that of open sun drying were better in terms of quality and drying time with a total saving of 7 hours.